Can Price Earning Ratio And Financial Distress Moderate Stock Returns : A Case Study Of The Property & Real Estate Sector In Southeast Asia - Sunaryo, Deni (International Journal of Science, Technology & Management, 2022)
Discussion leads to the effect of Net Profit Margin, Quick Ratio, and Debt to Total Asset Ratio on Stock Return Moderated by Price Earning Ratio and Financial Distress. Therefore, this study aims to determine the effect of Net Profit Margin, Quick Ratio, and Debt to Total Asset Ratio on Stock Return Moderated by Price Earning Ratio and Financial Distress. This study uses the object of the Property & Real Estate sub-sector companies on the Southeast Asian Stock Exchange for the period 2012-2020. The population in this study are all Property & Real Estate sub-sector companies listed on the Southeast Asian Stock Exchange with a total population of 430 companies, and the sample taken by the researcher is 12 companies. the following conclusions, namely Net Profit Margin, Debt to Total Asset Ratio partially does not have a significant effect on stock returns in the property and real estate sub-sector listed on the Southeast Asian Stock Exchange. Quick Ratio partially has no significant effect on stock returns in the property and real estate sub-sector listed on the Southeast Asian Stock Exchange. Net Profit Margin, Quick Ratio, and Debt to Total Asset Ratio simultaneously significant effect on stock returns in the property and real estate sub-sector listed on the Southeast Asian Stock Exchange. Price Earning Ratio, Price Earning Ratio, Price Earning Ratio does not moderate Net Profit Margin on Stock Return in the property and real estate subsector listed on the Southeast Asian Stock Exchange. Financial Distress does not moderate Net Profit Margin, Quick Ratio, Debt to Total Asset Ratio on Stock Returns in the property and real estate sub-sector listed on the Southeast Asian Stock Exchange.